Pharmacological effect of synobiotic and phytobiotic in kidney function and some blood parameters of chicken - Kamel O. I., Marwa; A. A. El-Komy, Ashraf; A. A. Farag, Enas (International Journal of Pharmacology and Toxicology, 2021)
The aim of this research was to study the effects of dietary supplementation of ‎synbiotic, phytobiotics and their mixture on kidney functions, some blood parameters and histological criteria of broilers. A total of 200 ‎broiler chicks were randomly chosen and divided into eight groups (25 birds in each). The first four groups were unvaccinated chicken which received a basal diet (group 1) or ‎the same diet supplemented with 1g synobiotic /kg body weight (group 2), 1g phytobiotic /kg body weight (group 3) and 1g ‎synobiotic plus 1g phytobiotic/kg body weight (group 4). The second four groups were vaccinated chicken and fed the same previous treatments with groups 5, 6, 7 and 8, respectively. Therapeutic dose of synobiotic and phytobiotic or their mixture (1ml/ kg. body weight) orally for 3 ‎successive days ‎tended to decrease uric acid and creatinine in unvaccinated and vaccinated chicken at 7, 14 and 21 day. In this study uric acid and ‎creatinine levels resulted in decrease, showing a significant improvement of kidney functions‎ ‎. Some different parameters of blood and histological criteria showed normal measurements with no adverse effect of treatments.
Keywords: Synobiotic; Phytobiotic; Vaccinated; Unvaccinated; Chicken.